2022
DOI: 10.1101/2022.09.27.22280385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multimodal intervention for Alzheimer’s disease results in multifaceted systemic effects reflected in blood and ameliorates functional and cognitive outcomes

Abstract: Introduction. Comprehensive treatment of Alzheimer's disease and related dementias (ADRD) requires not only pharmacologic treatment but also management of existing medical conditions and lifestyle modifications including diet, cognitive training, and exercise. The Coaching for Cognition in Alzheimer's (COCOA) trial was a prospective randomized controlled trial (RCT) to test the hypothesis that a remotely coached multimodal lifestyle intervention would improve early-stage Alzheimer's disease (AD). AD results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Deployment of such a protocol has led to anecdotal reports of cognitive improvement in patients with AD at the stage of mild cognitive impairment (MCI) as well as dementia [15][16][17], and more recently successful proof-of-concept trials (i.e., leading to improved cognition, not simply slowing decline) [13]. A somewhat similar approach has been reported by Roach and colleagues [18], as well as by Isaacson and colleagues [19].…”
Section: Introductionmentioning
confidence: 76%
“…Deployment of such a protocol has led to anecdotal reports of cognitive improvement in patients with AD at the stage of mild cognitive impairment (MCI) as well as dementia [15][16][17], and more recently successful proof-of-concept trials (i.e., leading to improved cognition, not simply slowing decline) [13]. A somewhat similar approach has been reported by Roach and colleagues [18], as well as by Isaacson and colleagues [19].…”
Section: Introductionmentioning
confidence: 76%
“…Studies have found that the transcriptome levels of two members of the IL17 family (IL17D and IL17RB) were upregulated in human AD astrocytes, suggesting a protective role of members of the IL17 family in AD through the antioxidant-protective Nrf2/IL17D axis against stress [36]. ILD17 is a candidate mediator for ameliorating memory performance trajectory and β-amyloid-induced neuroinflammation in AD [37,38].…”
Section: Discussionmentioning
confidence: 99%